Globalization, Gender, and the Family - Wolfgang Keller; Hale Utar (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper shows that globalization has far-reaching implications for the economy's fertility rate and family structure because it influences work-life balance. Employing population register data on all births, marriages, and divorces together with employer-employee linked data for Denmark, we show that lower labor market opportunities due to Chinese import competition lead to a shift towards family, with more parental leave and higher fertility as well as more marriages and fewer divorces. This shift is driven largely by women, not men. Correspondingly, the negative earnings implications of the rising import competition are concentrated on women, and gender earnings inequality increases. The paper establishes the market- versus family choice as a major determinant of trade adjustment costs. While older workers respond to the shock rather similarly whether female or male, for young workers the family response takes away the adjustment advantage they typically have–if the worker is a woman. The female biological clock–low fertility beyond the early forties–is central to this gender difference in adjustment, rather than the composition of jobs or workplaces, as well as other potential causes.
Keywords: F16; F66; J12; J13; J16; 330; fertility; earnings inequality; marriage; divorce; import competition; gender gap